Overall and Multiphasic Findings of the Prostate, Lung, Colorectal and Ovarian (PLCO) Randomized Cancer Screening Trial - Prorok, Philip C.; Wright, Patrick; Riley, Thomas R.; Kramer, Barnett S.; Berg, Christine D.; Gohagan, John K. (Reviews on Recent Clinical Trials, 2018)
Background: Screening tests are typically evaluated for a single disease, but multiple tests for multiple diseases are performed in practice. The Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial assessed testing for four cancers simultaneously and can be viewed as a multiphasic cancer intervention. This paper presents overall and multiphasic findings of this trial. Methods: The PLCO trial was a randomized multi-center trial conducted at ten screening centers in the US. Participants were 76,682 men and 78,215 women ages 55 - 74 and free of the target cancers at trial entry. Screening tests were PSA and digital rectal examination for prostate cancer, chest x-ray for lung cancer, flexible sigmoidoscopy for colorectal cancer, CA125 and transvaginal ultrasound for ovarian cancer. Outcomes and harms of screening were assessed including compliance, test results, incidence, mortality, false positives and overdiagnosis. Results: Screening compliance was 82%, 72,820 (8%) of 906,064 exams were positive, the overall PPV was 4.2% and the cancer detection rate was 3.38/1000. A mortality reduction was observed only for colorectal cancer (RR 0.72, 95% CI 0.61 - 0.85) with no effect on all-cause mortality. Ninety-six percent of positive exams were falsely positive and there was a suggestion of overdiagnosis of prostate and possibly ovarian cancers. Multiphasic testing resulted in 7374 men and 2748 women experiencing multiple false positive results from multiple types of tests. Conclusion: Multiphasic cancer screening led to reduced mortality for one target cancer and imposed a burden on the health care system that included substantial false positives and likely overdiagnosis.
Keywords: ovary